القضاء الإداري في الجزائر ودوره في حماية حرية الصحافة - خضير, رشيد (University of Eloued جامعة الوادي, 2018)
The study discusses the role of administrative courts in protecting freedom of the press in Algeria. The study clarifies the role of the press authority in granting licenses for the issuance of newspapers. The study shows the role of administrative courts in supervising the decision to grant licenses as well as in supervising the administrative ban of newspapers in normal and exceptional circumstances.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: القضاء الإداري، حرية الصحافة، الجزائر